Tumbuhan dalam Perspektif Al-Qur'an dan Hadis: Kajian Teologis dan Saintifik - Alihan Satra; Yosa Marhawati; Nabilla Azzahra (Advances In Education Journal, 2026)
This study examines the verses of the Qur’an and the Hadith of Prophet Muhammad (peace be upon him) related to plants and their relevance to human life. In Islamic perspective, plants are understood as one of the signs of Allah’s greatness (ayat kauniyah) that play an essential role in human life, serving as sources of food, medicine, and environmental balance. This research uses a qualitative method with a library research approach, collecting data from various journals, books, and scientific articles without field observation. The findings show that the Qur’an frequently describes the process of plant growth as evidence of Allah’s power, as stated in Surah Al-An’am, Surah Yasin, and Surah Al-Baqarah. The Hadith also emphasize that planting and caring for trees are considered acts of worship and continuous charity (sadaqah jariyah) as long as they benefit living beings. Furthermore, plants are closely related to modern sciences such as biology and ecology, indicating harmony between divine revelation and scientific knowledge. This study highlights that plants have not only biological value but also spiritual, ecological, and social significance in human life. In conclusion, Islam strongly emphasizes the importance of preserving, protecting, and wisely utilizing plants as part of human responsibility as khalifah (vicegerent) on earth.